Implementasi Aplikasi Surat Perintah Tugas dan Perjalanan Dinas pada Dinas Ketahanan Pangan Kalimantan Tengah - Sam'ani Sam'ani; Rosmiati Rosmiati; Ferdiyani Haris; Mochammad Ichsan; Siti Maryamah; Suparno Suparno; M. Haris Qamaruzzaman (Jurnal Medika: Medika, 2026)
The administrative management of official assignment letters and official travel orders at the Central Kalimantan Provincial Food Security Office was previously conducted manually, resulting in inefficiencies, data redundancy, and difficulties in document retrieval. This community service activity aimed to implement a website-based application for managing official assignment letters and official travel orders to improve administrative effectiveness and accuracy. The method used in this activity was the direct implementation of the application through system installation, configuration, and operational use within the partner institution. The implementation process included initial coordination, application deployment, data input, and utilization by administrative staff. The results of the implementation showed that the application was able to streamline the process of recording, managing, and archiving official assignment and travel documents. Administrative tasks became more structured, data retrieval was faster, and the risk of data loss was reduced. In conclusion, the implementation of the website-based application successfully supported the improvement of administrative performance and can be sustainably utilized to support official travel management at the Central Kalimantan Provincial Food Security Office.